General population based study of the impact of tricyclic and selective serotonin reuptake inhibitor antidepressants on the risk of acute myocardial infarction. Issue 4 (16th March 2005) - Tata, L J; West, J; Smith, C; Farrington, P; Card, T; Smeeth, L; Hubbard, R
Abstract : Objective: To investigate the impact of tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) on the risk of first acute myocardial infarction (MI). Design: Case–control analysis and a self controlled case series. Setting: 644 general practices throughout England, Scotland, Wales, and Northern Ireland. Patients: Over 60 000 cases of MI and 360 000 age, sex, and practice matched controls randomly selected from the UK General Practice Research Database. Main outcome measures: Matched odds ratios and incidence rate ratios estimating whether there is an acute or prolonged increased risk of MI after exposure to TCA and SSRI drugs and individual drugs within these families. Results: Case–control analysis found an initial increased risk of MI after TCA exposure (for example, at 1–7 days after the first dothiepin prescription: odds ratio (OR) 1.90, 95% confidence interval (CI) 1.15 to 3.14) or SSRI exposure (for example, at 1–7 days after first fluoxetine prescription: OR 2.59, 95% CI 1.44 to 4.66). In the self controlled analysis the equivalent risk estimates were an incidence rate ratio of 1.43, 95% CI 0.92 to 2.22 for dothiepin and an incidence rate ratio of 1.66, 95% CI 1.01 to 2.71 for fluoxetine. Conclusions: Antidepressant prescriptions are associated with an increased risk of MI. The size of these effects is similar for TCA and SSRI exposures; however, the lack of specificity between types of antidepressants and the lower risks found in the self controlled analysis suggest that these associations are more likely due to factors relating to underlying depression and health services utilisation than to specific adverse drug effects.